The Analysis of Epos (Electronic Point-of Sale) System in Posh Café & Resto Medan: Analisis Sistem Epos (Electronic Point-of Sale) di Posh Café & Resto Medan - Ericky Benna Perolihin Manurung; Jasael Simanullang; Erni Dewi Munthe (Universitas Muhammadiyah Palu, 2023)
Since a long time ago, food service has been social part of human history. The idea of selling food for profit existed as far as earliest civilization. Before transportation emerged, peasants and farmers carried their livestock to the urbanmarket, often they traveled to a vast distance and several days at a time. This was the beginning of restaurant. Nowadays, restaurant is different, it varies from the type of the restaurant, the food style until the way of service. There are variations of restaurant types from fast food restaurant to fine dining restaurant. Writer also explain about the company background based on the internshipprogram. The restaurant that has operated for almost 2 years yet still to excel in maximizing a good and productive restaurant. In this opportunity, writer is interested to understand about the way oservice in a restaurant. Conventionally, taking orders were recorded manually, such as handwritten on a piece of paper or even depend solely in mind. However, within time, technology emerged. To date, there a lot of Point-of Sales system available to be operated by the restaurant. The system has a lot of features and prevents mistakes and errors a conventional way of service might occur. The writer would like to find out the steps of implementing the system, features available, and the usage in day-to-day activities in the restaurant. This final is written based on the writer’s experience working in an internship program in Posh Café & Resto for 4 months. The writer expect this project would serve as suggestion and recommendation to the restaurant as well as for readers to find out detailed information about Point-of-Sales system in Posh Café & Resto.